Observing the factors affecting the development of age-friendly cities in Malaysia / Sumarni Ismail ... [et al.] - Ismail, Sumarni; Abdulkaareem Salih, Sarah; Zainal Abidin, Izzati; Hamid, Tengku Aizan; Syed Abdul Rashid, Sharifah Norazizan; Ahmadad, Siti Anom; Ibrahim, Rahimah (2022)
Malaysia is currently experiencing two demographic transitions, both population ageing and urbanisation. By 2050, Malaysia will be an aged nation with a declining number of younger ages and a rising proportion of older adults ages 60 and over, with a vast population living in the urban areas. Therefore, this study aimed to evaluate and understand the current situation of the physical and social environment in Taiping City in line with WHO guidelines on age-friendly cities. The present study employed an onsite observations approach conducted in five sites in Taping City in November 2021 from 07:00 am to 06:59 pm. The five sites selected in the central area of Taiping near Taiping Lake Gardens include the traditional wet market Taiping, Taiping Lake Garden, Taiping Zoo Park, Daerah Taiping Mosque, and Taiping Municipal Council. The results indicated sound social interaction, inclusion, and cooperation in the City that meets the age-friendly social environment. However, the current built environment did not fully meet the physical environment of an age-friendly city, especially in the traditional commercial sites. Most of the spaces in Taiping City provided easy access and facilities to older adults. However, there was a lack of access for wheelchair users and disabled people, especially in commercial buildings. The current study contributed information and recommendations about the social and physical environments affecting enhancing age-friendly cities in Malaysia. Hence, the study's findings are of great importance for policymakers, Perak local authorities, architects, urban planners, and researchers in creating age-friendly cities in Malaysia.